1996
DOI: 10.1021/ic960859a
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of CB9H10- with Electrophiles, Including the Regioselective Mono- and Dihalogenation of the Lower Belt

Abstract: The 11B NMR spectrum of CpFe(CO)2(CB9H10) dissolved in dichloromethane shows the presence of two isomers in a 75:25 ratio. In the predominant isomer, the C 4 v -symmetry CB9H10 - anion is coordinated to the iron atom via the B10−H10 bond (the antipodal B−H bond). In the less abundant isomer, the CB9H10 - anion is coordinated to the iron atom via the B6−H6 bond, one of four equivalent B−H bonds (the lower-belt B−H bonds) adjacent to B10−H10. In spite of the preference of the electrophilic cation [CpFe(CO)2]+ f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 44 publications
0
41
0
Order By: Relevance
“…[42] Results and Discussion Synthesis and structures: Silver(i) salts of monoanionic carborane anions are readily prepared and are air stable and useful synthons for subsequent reactions. For example, they can be used in silver salt metathesis reactions to introduce a carborane anion into a metal×s coordination sphere [23,25,29,43,44] or to generate synthetically useful salts. [28] In addition they often have significant solubility in aromatic solvents compared with other cations, facilitating more complete characterisation of the cation/anion pair.…”
Section: Introductionmentioning
confidence: 99%
“…[42] Results and Discussion Synthesis and structures: Silver(i) salts of monoanionic carborane anions are readily prepared and are air stable and useful synthons for subsequent reactions. For example, they can be used in silver salt metathesis reactions to introduce a carborane anion into a metal×s coordination sphere [23,25,29,43,44] or to generate synthetically useful salts. [28] In addition they often have significant solubility in aromatic solvents compared with other cations, facilitating more complete characterisation of the cation/anion pair.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that halogenation of these two anions occurs also initially at the 6-position [2,20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Iodination as well as other halogenation reactions of ten-vertex analog 8 exhibits high regioselectivity for the 6 position and the desired 10-iodo-1-carba-closo-decaborate (42) is formed in less than 2% yield 130 . It has been proposed that the latter may be obtained by thermal rearrangement of the kinetic 6-isomer 43 isolated in 51% yield 130 .…”
Section: Boron Substitutionmentioning
confidence: 99%
“…It has been proposed that the latter may be obtained by thermal rearrangement of the kinetic 6-isomer 43 isolated in 51% yield 130 .…”
Section: Boron Substitutionmentioning
confidence: 99%